Corporate Customer Behaviour & Indian Hardware Market (with Special Reference to HCL Infosystem Ltd) - Koti Reddy, T.; Sarkar, Soumya Kanti (Indian Journal of Marketing, 2009)
In today’s rein of globalized consumerism, understanding the consumer behavior has attained paramount significance. Consumer behavior is the study of how individuals make decisions to spend their available resources, namely time, effort and money on consumption related items. The heterogeneity among consumers across markets makes understanding consumer behavior an intricate and challenging task. In modern era of brisk economic development; the organizational market above all, has gained prime significance. With constantly changing business environment, the dynamics of industrial markets more than any other form of market is evolving most rapidly. Companies in this form of market have thus realized the significance of reduction of customer centric product development, technological advancement and effective innovation. The primary objective of this project was to decipher to the extent possible, the intricacies of the buying behavior of the corporate customer in the IT hardware market and to study and understand the major factors affecting the same. The research was facilitated through both primary data analysis as well as secondary study. The report summarizes the findings in the form of a statistical analysis. SPSS software has been used to interpret the different statistical relationships among the variables studied. The analysis included Correlation&Regression, Discriminant Analysis and Factor analysis. Besides, the report incorporates a comparative analysis of the different business parameters among the market leaders. The findings have revealed a stark disapprobation between the current market scenario and the customer preferences. It has become evident through the study that Service and Technological expertise are the major influencing factors in the IT hardware industry. Interestingly, Price is only a secondary concern in organizational buying decision. A high correlation has also been observed between Loyalty, Service, Customization and the tenure of association.